ISTANBUL TRAFFIC PROBLEM: EXPERT OPINIONS - Cal, Murat; Onden, Ismail; Samasti, Mesut; Eldemir, Fahrettin (FUTURE ACAD, 2017)
Istanbul is Europe's most populous metropolis. The population of the city has increased sevenfold in the last 50 years and the usage of the area has increased threefold. As a result of this extreme growth, the most important problem of Istanbul today becomes traffic. Therefore, transportation investments are the most important part of the city budget. There are different solution propositions and theories of experts on this problem. Within the scope of the study, 3 different workshops were carried out in order to reflect the opinions of the experts. In these workshops, flexible methods, traffic planning, strategic planning, socioeconomic interaction and intra-urban transportation systems and environmental impacts are discussed in tired transportation planning. More than 200 invited experts attended the workshops. The article summarizes the views that stand out in these workshops. It has been found that safe journey, speed, quality of service, comfort and low cost are all in the first place in terms of both passengers' public transportation view criteria and management's public transportation planning criteria. (C) 2017 Published by Future Academy www.FutureAcademy.org.uk
Keywords: Traffic planning; workshops; SWOT; problem detection; Istanbul; Social Sciences - Other Topics